(untitled) (XXI Century. Spanish Literature and Culture, 2016)
José Luis Alonso de Santos wrote Los Conserjes De San Felipe (Cadiz 1812) in 2012. In that play we can see traditional Spanish elements that appear in Literature many times, such as liberalism, Lope de Vega´s literary resources, the word “intrahistoria”, whose creator was Unamuno, the word “esperpento”, that was defined by Valle-Inclan, or Goya´s opinion about the war. In this study, we connect all those elements and defend that two hundred years are not enough to 1812 Constitution, because its ideas are valid nowadays.